lvq-trammel for rozpіznavannya tehnіchnogo going avіatsіynih gazoturbіnnih dvigunіv - Абдуллаєв, П.Ш.; Мірзоєв, А.Д.; Якушенко, О.С. (Proceedings of National Aviation University (archive), 2007)
In the paper the problem of LVQ-network using for identification of aircraft gas turbine engines technical condition is considered. The results of LVQ-network training and using for aircraft gas turbine engines technical condition identification are given